Study of Stiffness Effect of Panel Zone on Ductility of RBS Joint - Oskouei, Amin Ghaznavi; Gerami, Mohsen (International Journal of Sustainable Construction Engineering and Technology, 2011)
Beam to column joint fractures on steel structures in Northridge earthquake produced some worries about the reliability of steel connections. Brittle fracture of bending joints indicated that ductility of construction materials doesn’t ensure structure ductility, and structure geometry, loading type, and other specifications influence structure behavior. Stress (strain) concentration due to seismic moment changes may prevent distribution of plastic zone around joint, and this can be a justification for joint brittle fracture. RBS joint is one that came after Northridge earthquake, which is known as dog bone joint. In this kind of joint, by minimizing section of beam flange near support area (in which possibility of plastic joint formation is more), plastic joint is transferred from column side and joint area to inside beam and at proper interval with joint. To design this joint and achieve the goal of formation and development of plastic hinge in reduced area, many parameters must be considered. Panel zone is one of the most effective parts of a rigid steel joint. Resistance and stiffness value of panel zone has a large effect on behavior and performance of joints. This paper studies these kinds of joints and effects of changes in panel zone using cross-shaped substructure and ANSYS software. Regarding to the studies it was indicated that weak panel zone doesn’t develop plastic hinge in beam, so collapses merely occurs in panel zone and joint area. In specimens with strong panel zone, because of elastic behavior of panel zone, all substructure energy is wasted in beam, so panel zone is not used efficiently.